Pharmacokinetics of Sublingual Buprenorphine and Naloxone in Subjects with Mild to Severe Hepatic Impairment (Child-Pugh Classes A, B, and C), in Hepatitis C Virus-Seropositive Subjects, and in Healthy Volunteers - Nasser, Azmi F.; Heidbreder, Christian; Liu, Yongzhen; Fudala, Paul J. (Clinical pharmacokinetics, 2015)
Background and Objectives Suboxone ® is a sublingual tablet of buprenorphine/naloxone, approved for the treatment of opioid dependence. The objective of this study was to quantify the impact of hepatic impairment or hepatitis C virus infection on the pharmacokinetics of buprenorphine or naloxone and their major metabolites. Methods Forty-three subjects received a single dose of a Suboxone 2.0/0.5-mg tablet. Blood samples were collected up to 168 h and pharmacokinetic parameters were calculated using non-compartmental analysis. Statistical analysis was performed using analysis of covariance. Results Pharmacokinetic parameters were derived from 33 subjects. Compared with healthy subjects, for patients with severe hepatic impairment, total and peak exposures increased to 281.4 % [90 % confidence interval 187.1–423.3] and 171.8 % [117.9–250.2] for buprenorphine, 1401.9 % [707.6–2777.5] and 1129.8 % [577.2–2211.4] for naloxone. For moderate hepatic impaired subjects, naloxone total and peak exposure increased to 317.6 % [164.9–611.5] and 270.0  % [141.9–513.9]. For buprenorphine, only total exposure increased to 163.9 % [110.8–242.3]. Changes in maximum observed plasma concentration, area under the plasma concentration-time curve from time zero to time of the last quantifiable concentration , and area under the plasma concentration-time curve from time zero to infinity of buprenorphine or naloxone in subjects with mild hepatic impairment or with hepatitis C virus infection were within twofold of those of healthy subjects. Serious adverse events were not observed. Conclusions Severe and moderate hepatic impairment significantly increased exposure of naloxone and to a lesser extent of buprenorphine. Therefore, buprenorphine/naloxone combination products should generally be avoided in patients with severe hepatic impairment and may not be appropriate for patients with moderate hepatic impairment. However, buprenorphine/naloxone products may be used with caution for maintenance treatment in patients with moderate hepatic impairment who have initiated treatment on a buprenorphine product without naloxone [Registered at ClinicalTrials.gov as NCT01846455]